HLA-G gene polymorphisms associated with susceptibility to rheumatoid arthritis disease and its severity in Brazilian patients. - Catamo, E; Addobbati, C; Segat, L; Sotero Fragoso, T; Domingues Barbosa, A; Tavares Dantas, A; de Ataíde Mariz, H; F da Rocha, L; Branco Pinto Duarte, A L; Monasta, L; Sandrin-Garcia, P; Crovella, S (Tissue Antigens, 2014)
We analyzed the possible association between human leukocyte antigen-G (HLA-G) genetic variants, supposed to regulate HLA-G expression, and the susceptibility to develop rheumatoid arthritis (RA) as well as its clinical manifestations. The 5'upstream regulatory region (5'URR) and 3'untranslated region (3'UTR) regions of the HLA-G gene were screened in 127 RA patients and 128 controls: 10 5'URR and 3 3'UTR HLA-G polymorphisms as well as two haplotypes were associated with risk for RA development, while a polymorphism in the 5'URR showed an association with the degree of disease activity. These findings, although the number of cases analyzed is limited and the P-values are modest, indicate a possible association between HLA-G gene polymorphisms and susceptibility to develop RA disease and its severity.
Keywords: 3' Untranslated Regions; 5' Flanking Region; Aged; Arthritis, Rheumatoid; Brazil; Disease Progression; DNA Mutational Analysis; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; HLA-G Antigens; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk